Image of the University Faculty in the View of Student Teachers - Kaļķe, Baiba; Baranova, Sanita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
In the article "Image of the University Faculty in the View of Student Teachers", the methods of survey and analysis of performance results are used to explore the image of university faculty in the experience of students of teacher education and pedagogics. An illustrative example is one of the key tools of education in pedagogics. It is significant to investigate the image of university faculty in teacher education because the university teacher also serves as a model of the professional pedagogical performance for student teachers in teacher education. The article highlights the visual image of the university teacher and their most typical personality traits that might have impacts on the future professional performance of student teachers.